First approach to the knowledge of Orthocentrus Gravenhorst, 1829 (Hymenoptera, Ichneumonidae: Orthocentrinae) in Colombia: Description of ten new species, addition of new records, and taxonomic key to Colombian species - Álvarez-Arellano, Diego; Palacios-Castro, Shirley (Zootaxa, 2026)
Historically, knowledge of Orthocentrinae in Colombia has been extremely limited. Thus, this study represents the first approach to the subfamily in the country through the genus Orthocentrus Gravenhorst, 1829, in which ten new species are described: O. cafetera sp. nov., O. carrilera sp. nov., O. jornalera sp. nov., O. lyda sp. nov., O. parcerita sp. nov., O. parchada sp. nov., O. pasillo sp. nov., O. pereirana sp. nov., O. santarrosana sp. nov., O. shirley sp. nov., new records are provided, and an identification key for all Colombian species is included.